Short-Chain Fatty Acid Receptors and Blood Pressure Regulation: Council on Hypertension Mid-Career Award for Research Excellence 2021. Issue 10 (1st August 2022) - Xu, Jiaojiao; Moore, Brittni N.; Pluznick, Jennifer L.
Abstract : The gut microbiome influences host physiology and pathophysiology through several pathways, one of which is microbial production of chemical metabolites which interact with host signaling pathways. Short-chain fatty acids (SCFAs) are a class of gut microbial metabolites known to activate multiple signaling pathways in the host. Growing evidence indicates that the gut microbiome is linked to blood pressure, that SCFAs modulate blood pressure regulation, and that delivery of exogenous SCFAs lowers blood pressure. Given that hypertension is a key risk factor for cardiovascular disease, the examination of novel contributors to blood pressure regulation has the potential to lead to novel approaches or treatments. Thus, this review will discuss SCFAs with a focus on their host G protein-coupled receptors including GPR41 (G protein-coupled receptor 41), GPR43, and GPR109A, as well as OLFR78 (olfactory receptor 78) and OLFR558. This includes a discussion of the ligand profiles, G protein coupling, and tissue distribution of each receptor. We will also review phenotypes relevant to blood pressure regulation which have been reported to date for Gpr41, Gpr43, Gpr109a, and Olfr78 knockout mice. In addition, we will consider how SCFA signaling influences physiology at baseline, and, how SCFA signaling may contribute to blood pressure regulation in settings of hypertension. In sum, this review will integrate current knowledge regarding how SCFAs and their receptors regulate blood pressure.